Theodicy and justice in modern Islamic thought the case of Said Nursi - Abu-Rabiʻ, Ibrahim M. (Ashgate Publishing Limited, 2010)
This book explores the theology and philosophy of the distinguished modern Muslim scholar and theologian Bediuzzaman Said Nursi [d.1960]. Nursi wrote in both Ottoman Turkish and Arabic and his life and thought reflected the transition of modern Turkey from an empire to a secular republic. The contributors to this volume shed new light on two major dimensions of Nursi's thought: theodicy and justice. Classical Muslim theologians debated these two important issues; however, we must consider the modern debate of these issues in the context of the radical political and social transformations of modern Turkey. Nursi explored these matters as they related to the development of state and society and the crisis of Islam in the modern secular nation-state. Nursi is the founder of a 'faith movement' in contemporary Turkey with millions of followers worldwide. In this book, distinguished scholars in Islamic, Middle Eastern, and Turkish Studies explore Nursi's thought on theodicy and justice in comparison with a number of western philosophers, theologians, and men of letters, such as Dante, Merton, Kant, and Moltman. This book presents an invaluable resource for studies in comparative religion, philosophy, and Islamic and Middle Eastern Studies